Perancangan Sistem Energi Terintegrasi Berbasis MPPT, Baterai 48V, dan Inverter untuk Pembangkit Listrik Tenaga Pico Hydro - Erwin Alvito; Dimas Fahim Alkahfi; Isac Ilham Akbar Habibi; Kholid Yovanda; Jenko Antofa Gasta; Naufal Adib Ramadhani (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2026)
Pico-hydro power plants (PLTPH) are renewable energy solutions suitable for rural areas with low water discharge. However, voltage fluctuations significantly affect battery charging stability. This research develops a 48V charging system using an MPPT converter combined with a DC–AC inverter and an Arduino-based monitoring system for cell voltage, current, and LiFePO₄ 15S battery protection. The system integrates a pico-hydro generator, three-phase rectifier, MPPT 60A module, 48V 50Ah battery, sinusoidal inverter, and BMS equipped with INA219 sensors and voltage dividers. Experimental results show MPPT efficiency of 90–98% under light loads, and the inverter delivers stable AC output for household consumption. The monitoring subsystem accurately measures per-cell voltage and triggers protection during overcharge and overdischarge scenarios. Overall, this integrated system is feasible and reliable for off-grid renewable energy applications in remote areas provide benefits to communities with limited resources. Overall, this system can be a model for effective and efficient renewable energy development to improve the quality of life of people in remote areas.